Acute or Delayed Systemic Administration of Human Amnion Epithelial Cells Improves Outcomes in Experimental Stroke. Issue 3 (March 2018) - Evans, Megan A.; Lim, Rebecca; Kim, Hyun Ah; Chu, Hannah X.; Gardiner-Mann, Chantelle V.; Taylor, Kimberly W.E.; Chan, Christopher T.; Brait, Vanessa H.; Lee, Seyoung; Dinh, Quynh Nhu; Vinh, Antony; Phan, Thanh G.; et al.
Abstract : Background and Purpose—: Human amnion epithelial cells (hAECs) are nonimmunogenic, nontumorigenic, anti-inflammatory cells normally discarded with placental tissue. We reasoned that their profile of biological features, wide availability, and the lack of ethical barriers to their use could make these cells useful as a therapy in ischemic stroke. Methods—: We tested the efficacy of acute (1.5 hours) or delayed (1–3 days) poststroke intravenous injection of hAECs in 4 established animal models of cerebral ischemia. Animals included young (7–14 weeks) and aged mice (20–22 months) of both sexes, as well as adult marmosets of either sex. Results—: We found that hAECs administered 1.5 hours after stroke in mice migrated to the ischemic brain via a CXC chemokine receptor type 4-dependent mechanism and reduced brain inflammation, infarct development, and functional deficits. Furthermore, if hAECs administration was delayed until 1 or 3 days poststroke, long-term functional recovery was still augmented in young and aged mice of both sexes. We also showed proof-of-principle evidence in marmosets that acute intravenous injection of hAECs prevented infarct development from day 1 to day 10 after stroke. Conclusions—: Systemic poststroke administration of hAECs elicits marked neuroprotection and facilitates mechanisms of repair and recovery. Abstract : Supplemental Digital Content is available in the text.